PEMBERIAN MOTIVASI UNTUK MENINGKATKAN PRESTASI BELAJAR BAHASA INDONESIA SISWA - Rusnanik Rusnanik (MEDIA DIDAKTIKA, 2015)
This study was aimed to describe (1) the motivation providing to the students, (2) the increase of students’ motivation, and (3) the improvement of sudents’ learning outcomes of Bahasa Indonesia through the motivation provision. The study was conducted in the sixth graders of the third graders of Deket Kulon, Deket – Lamongan, which was designed with classroom action research (PTK) within two cycles. Each cycle was done through four stages: planning, implementation, observation and reflection. The results showed that the students’ motivation achievement has increased from cycle I to cycle II. Similarly, the students’ learning outcomes of bahasa Indonesia also increased from an average of 84.8 in the first cycle increased to 86.2 in second cycle. The result suggested that the motivation can improve the sixth graders’ learning achievement of bahasa Indonesia.